Atom optics and space physics : proceedings of the International School of Physics "Enrico Fermi", course CLXVIII, Varenna on Lake Como, Villa Monastero, 3-13 July 2007 - Arimondo, E.; Ertmer, W.; Schleich, Wolfgang; Rasel, E. M. (Proceedings of the International School of Physics "Enrico Fermi" ;, 2009)
Discusses the field of atom optics and interferometry with its aspects ranging from fundamental physics to applications and the theory of relativity. This book offers an introduction to atom optics and Bose-Einstein condensation. It also discusses the theoretical foundations of cold atom interferometers and their use to test gravity.